PENGARUH ASIMETRI INFORMASI DAN STRUKTUR KEPEMILIKAN PERUSAHAAN TERHADAP PRAKTIK MANAJEMEN LABA PADA PERUSAHAAN PERBANKAN PERIODE 2009-2011 - B41109041, Ekajayanti (Jurnal KIAFE, 2013)
This study aims to investigate the relationship between information asymmetry and ownership structure of earnings management. Ownership structure is distinguished into two, family ownership and institutional ownership. The population of this research is public Indonesian banking firms listed on Indonesia Stock Exchange (IDX) in 2009-2011 by using 17 samples and 51 observations. Study uses secondary data and analyze method is multiple regression. Earnings management is measured by using modified Jones Model. Then, mean bid ask spread is used as the proxy of information asymmetry. Result indicates that first, information asymmetry has no significant effect with earnings management. Second, family ownership has positive and significant enough effect with earnings management. Third, institutional ownership also has positive and significant enough effect with earnings management. Keywords: information asymmetry, family ownership structure, institutional ownership structure, earnings management, mean bid ask spread